2015
DOI: 10.1021/acs.macromol.5b00158
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Semiconducting Behaviors of New Alternating Dithienyldiketopyrrolopyrrole–Azulene Conjugated Polymers by Varying the Linking Positions of Azulene

Abstract: Three new conjugated polymers DPPA1, DPPA2, and DPPA3 with dithienyldiketopyrrolopyrrole (DPP) and azulene moieties were synthesized and characterized. The five-membered rings of azulene are connected with DPP in DPPA1 and DPPA2, whereas the seven-membered ring of azulene is incorporated into the backbone of DPPA3. The LUMO energy of DPPA3, which was determined on the basis of the respective cyclic voltammograms and absorption spectra, is lower than those of DPPA1 and DPPA2. OFETs were successfully fabricated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 76 publications
0
42
0
1
Order By: Relevance
“…The construction of alternating donor (D)–acceptor (A) structures might afford high‐performance semiconducting polymers. Three azulene‐containing conjugated D–A polymers, 30 a – c (Figure ), with dithienyldiketopyrrolopyrrole units were reported by Zhang and co‐workers . It was demonstrated that the semiconducting behavior of these three polymers can be modulated by altering the connectivity of the azulene units in the polymer backbones.…”
Section: Azulene‐based Materials For Organic Field‐effect Transistorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The construction of alternating donor (D)–acceptor (A) structures might afford high‐performance semiconducting polymers. Three azulene‐containing conjugated D–A polymers, 30 a – c (Figure ), with dithienyldiketopyrrolopyrrole units were reported by Zhang and co‐workers . It was demonstrated that the semiconducting behavior of these three polymers can be modulated by altering the connectivity of the azulene units in the polymer backbones.…”
Section: Azulene‐based Materials For Organic Field‐effect Transistorsmentioning
confidence: 99%
“…This is consistent with a previous study on the modulation of optoelectronic and stimuli‐responsive properties of azulene‐based polymers by tuning the connecting positions of azulene moieties in the polymeric main chain . For polymers 30 a and 30 b , in which the azulene moieties were connected at electron‐rich five‐membered rings, their OFET devices exhibited unipolar p‐type semiconducting properties with hole mobilities of 0.97 and 8×10 −2 cm 2 V −1 s −1 , respectively . In comparison with 30 a and 30 b , 30 c with the electron‐deficient seven‐membered ring of azulene incorporated into the polymeric backbone has a lower LUMO energy as well as a better spread LUMO density, demonstrating ambipolar semiconducting behavior with hole and electron mobilities of up to 6.2×10 −2 and 2.1×10 −2 cm 2 V −1 s −1 , respectively …”
Section: Azulene‐based Materials For Organic Field‐effect Transistorsmentioning
confidence: 99%
“…18 Another ligand, tri(o-tolyl)phosphine (P(o-tol)3) was also attempted to prepare PDPP-T-TQ as it was reported that polymers with Mn higher than 10 kg mol -1 could be produced when using the Pd2(dba)3/P(o-tol)3 catalyst system in Suzuki coupling based on DPPdiboronic ester. [23][24][25] The Mn of resulting polymer (6.3 Kg mol -1 , PDI: 2.9) is however slightly lower in comparison with that using the ligand of (t-Bu)3P·HBF4. After introducing one more electron-rich thiophene onto monomer 4 at both sides, the steric hindrance between DPP and monomer 7 was reduced so that the PDPP-3T-TQ possessed a higher Mn than the other two polymers.…”
Section: Synthesis and Characterizationmentioning
confidence: 91%
“…In view of the easy availability and low cost of some azulene derivatives, it is reasonable to speculate that azulene might be a simple but promising D structural unit to construct OPV donor materials with low bandgaps, high V oc and good hole mobilities. However, up until now, there have only been two relative reports on azulene‐containing OPV polymers . Although plenty of azulene‐based small molecules have been reported, to the best of our knowledge, hitherto none have been applied to the OPV field.…”
Section: Methodsmentioning
confidence: 99%